(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To study the clinical, paraclinical characteristics and pregnancy outcomes in pregnant women with more than 2 cesarean sections at Can Tho Gynecology Obstetrics Hospital. Materials and methods: A cross-sectional study of 92 pregnant women who came for examination and were hospitalized at Can Tho Gynecology Obstetrics Hospital from May 2023 to September 2024. Results: The average age of pregnant women was 33.4 ± 4.9 years old; the oldest was 43 years old and the youngest was 21 years old. The rate of pregnant women living in rural areas was 2.67 times higher than in urban areas (72.8% compared to 27.2%). Pregnant women who had had 2 cesarean sections accounted for the highest rate (84.9%). There were 8 cases of placenta previa, of which 6 cases had placenta accreta spectrum. The gestational age group of 38 weeks to 38 weeks and 6 days had the highest rate (57.6%) at the time of termination of pregnancy. The majority had cesarean sections (97.8%). There were 8 cases (8.8%) requiring blood transfusion during cesarean section. Conclusions: The rate of pregnant women who have had 2 cesarean sections is high.